AB0625 Effect of one cycle of rituximab in the lipid profile of patients with refractory systemic lupus erythematosus (SLE). (23rd January 2014) - Nieves-Martín, L.; Pego, J.M.; Marenco, J.L.; Carreño, L.; Galindo, M.; Tomero, E.; Rúa-Figueroa, I.; Hernández, B.E.; Narváez, J.; Úcar, E.; Olivé, A.; Zea, A.; et al.
Abstract : Objectives: To investigate lipidic changes that occurs with Rituximab(RTX) in refractory SLE-patients. Methods: Multicenter, retrospective, longitudinal study. All SLE-patients from LESIMAB study with basic lipid data at baseline and 6±3 months after the first cycle of RTX were included. Cardiovascular risk factors (CVRF), comorbidities and treatments were collected, including lipid profile. Results: 101 patients were included (91% women; age 38.7±12.1yrs). The duration of SLE was 7.1±6.1yrs, median of severe organ-systems affected was 2.0 (range, 0-6), and median of previous drugs against SLE was 5 (range, 2-9). The Charlson-age comorbidity index was of 2.0±1.2 and the number of classic CVRF was 1.1±0.1. The baseline SLEDAI was 14.2±9.6. RTX was administrated with other drugs, including corticosteroids (n=101), hydroxychloroquine (HCQ; n=48), and statins (n=16). As it shows the table, the mean of lipid profile at baseline was good and these values were similar between patients with concomitant HCQ. The patients who were receiving statins had worse baseline lipid profile (CT, p=0.028; LDL, p=0.011; VLDL, p=0.040; TG, p=0.040).After 6±3 months of RTX treatment, the global lipids values didn't change significantly (Table). However, the patients who achieved a good clinical response (partial or complete) in the SLE activity their lipid profile also improved [TC (p=0.004), HDL (p=0.004), VLDL (p=0.041) and TG (p=0.041)] and a correlation between improvement of SLEDAI (delta-SLEDAI at 24w from baseline, 9.8±9.5) and the improvement of the lipid profile after 24w was observed: delta-CT 24w (r=0, 349; p<0, 001), delta-TG 24w (r=0, 366; p<0, 001) y delta-VLDL 24w (r=0, 366; p<0, 001). Although the needs of corticosteroids decreased (delta-prednisone after 24w was 21.0±63.8mg/d), it didn't influence in the lipid improvement, since there was no correlation between delta-prednisone after 24w and improvement in lipid profile. Conclusions: RTX doesn't seem to have an intrinsic effect in the lipid profile from patients with refractory SLE. However, a good control of the disease activity promotes a improvement in lipid profile. Disclosure of Interest: None Declared